2020
DOI: 10.1016/j.stemcr.2020.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Developmental IL-6 Exposure Favors Production of PDGF-Responsive Multipotential Progenitors at the Expense of Neural Stem Cells and Other Progenitors

Abstract: Interleukin-6 (IL-6) is increased in maternal serum and amniotic fluid of children subsequently diagnosed with autism spectrum disorders. However, it is not clear how increased IL-6 alters brain development. Here, we show that IL-6 increases the prevalence of a specific platelet-derived growth factor (PDGF)-responsive multipotent progenitor, with opposite effects on neural stem cells and on subsets of bipotential glial progenitors. Acutely, increasing circulating IL-6 levels 2-fold above baseline in neonatal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…This reflects the abnormal cortical structure seen in ASD patients, where there is an increase in the numbers of immature neurons and glial cells in certain areas of the brain [107,116]. Moreover, elevated levels of IL-6 have been shown to increase the proliferation of platelet-derived growth factor (PDGF)-and fibroblast growth factor 2 (FGF-2)-responsive multipotential progenitors (PFMP) in developing mice brain [119]. The PFMPs express IL-6Rα and GP130 receptors required for downstream IL-6 signalling, and it was noted that IL-6 activates pSTAT3 in these cells [119].…”
Section: Interleukin-6mentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects the abnormal cortical structure seen in ASD patients, where there is an increase in the numbers of immature neurons and glial cells in certain areas of the brain [107,116]. Moreover, elevated levels of IL-6 have been shown to increase the proliferation of platelet-derived growth factor (PDGF)-and fibroblast growth factor 2 (FGF-2)-responsive multipotential progenitors (PFMP) in developing mice brain [119]. The PFMPs express IL-6Rα and GP130 receptors required for downstream IL-6 signalling, and it was noted that IL-6 activates pSTAT3 in these cells [119].…”
Section: Interleukin-6mentioning
confidence: 99%
“…Moreover, elevated levels of IL-6 have been shown to increase the proliferation of platelet-derived growth factor (PDGF)-and fibroblast growth factor 2 (FGF-2)-responsive multipotential progenitors (PFMP) in developing mice brain [119]. The PFMPs express IL-6Rα and GP130 receptors required for downstream IL-6 signalling, and it was noted that IL-6 activates pSTAT3 in these cells [119]. right) which consequently produce IL-6 in the maternal compartment of the placenta.…”
Section: Interleukin-6mentioning
confidence: 99%
“…In addition, plateletderived growth factor (PDGF) is crucial for cell survival and proliferation including MSCs and other progenitors. 36 The co-transplantation of MSCs and TCs had better therapeutic effects on ALI development, during which TCs could promote the migration and infiltration of MSCs into the lung. The conditioned medium containing nutrient factors also showed effectiveness in protecting lung against ALI.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that transiently increasing systemic levels of IL-6 in neonatal mice affects the balance of stem cells and progenitors within the SVZ and an earlier study had shown that increased circulating levels of IL-6 affects neurogenesis in the hippocampus (Monje et al, 2003;Kumari et al, 2020). Therefore, we postulated that neurogenesis and gliogenesis would be abnormal in IL-6 injected (Rx) mice.…”
Section: Transiently Elevating Circulating Il-6 Reduces Gliogenesis In the Corpus Callosum And Amygdala And Neurogenesis In The Hippocampmentioning
confidence: 99%
“…These progenitors will produce neurons, astrocytes and oligodendrocytes that populate several late developing brain structures that are relevant to the behavioral deficits seen in neurodevelopmental disorders. The SVZ and SGZ rapidly expand during the early 3rd trimester of human development (Monje et al, 2003;Covey et al, 2011;Wei et al, 2011;Storer et al, 2018;Kumari et al, 2020), and in early postnatal development in mice (Semple et al, 2013;Salmaso et al, 2014). While MIA studies conducted to date have manipulated the immune system at mid-gestation, it remains to be established whether elevating IL-6 postnatally in mice is sufficient to alter the trajectory of neural development and elicit behavioral aberrations.…”
Section: Introductionmentioning
confidence: 99%